(untitled) (Biodiversitas Journal of Biological Diversity, 2015)
Panal CLT, Opiso JG, Opiso G. 2015. Conservation status of the Family Orchidaceae in Mt. Sinaka, Arakan, North Cotabato, Philippines. Biodiversitas 16: 213-224. This study determines the conservation status of the family Orchidaceae, as present on Mt. Sinaka, Arakan, North Cotabato, Philippines. A thorough survey and alpha taxonomy was done, from base to peak of the mountain. Identification of the specimens and assessment of their conservation status was based on the IUCN Red List of Threatened Plants 2013.2 and National List of Threatened Philippine Plants of Fernando et al. (2008). Based on the result conducted on October 2013-March 2014, out of 59 identified species found in the area, 12 species are widespread, 22 are endemic, 1 vulnerable, 1 critically endangered (Paphiopedilum adductum), 1 endangered (Corybas sp.), 2 least concerned species, and 20 unassessed species (not yet assessed by the IUCN). It has been also noted that there are probably some new species, which need thorough study for further identification. The result calls for a desperate need for conservation. Facts from this study helps in addition to the existing wildlife conservation of flora in Mt. Sinaka and to the other forested mountains in Mindanao, the Philippines.